STRATEGI PEMASARAN DALAM MENGHADAPI PERSAINGAN USAHA PRESPEKTIF ETIKA BISNIS ISLAM - Hayatul Millah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2020)
ABSTRACT The purpose of this research is to find out the marketing strategy of BMT UGT Sidogiri Kraksaan. The other purpose of this research is to know the Islamic business ethics towards the implementation of marketing strategy in BMT UGT Sidogiri Kraksaan. The type of this research is qualitative research with a case study approach. The results of this study showed that supporting factors in the BMT UGT Sidogiri Kraksaan include external environmental factors and internal factors. The factors relating to the internal environment include targeting, positioning and segmentation, while other supporting factors in the external environment BMT UGT Sidogiri Kraksaan analyzes what are the weaknesses, strengths, opportunities and threats that occur in the cooperative environment. BMT UGT Sidogiri Kraksaan uses a marketing mix strategy which includes targeting, place strategies, pricing strategies and promotional strategies. Based on the results of the research in the Islamic business ethics, BMT UGT Sidogiri Kraksaan concluded that the strategy was conducted at the BMT UGT Sidogiri Kraksaan in accordance with the principles of Islamic business ethics, because in each process, the cooperative BMT UGT Sidogiri Kraksaan Foundation on the concept of sharia and the promotion in its products is not exaggeration, while the price carried out by the cooperative BMT UGT Sidogiri Kraksaan is using a system for the outcome of which the cooperative and the customer equally benefited , in promoting its products cooperatives BMT UGT Sidogiri Kraksaan is not exaggerating, promoting it according to the quality and procedure that has been promised by BMT UGT Sidogiri Kraksaan.